PENGARUH KELONGGARAN KATUP TERHADAP TEKANAN KOMPRESI PADA SEPEDA MOTOR YAMAHA MIO TAHUN 2005 - Asrofiq Asrofiq; Basmal Basmal; Sidiq Supriyanto (Pendidikan Vokasional Teknologi Otomotif, Universitas PGRI Yogyakarta, 2026)
Valves are vital components in internal combustion engines that regulate the intake of air-fuel mixtures and the exhaust of combustion gases. Improper valve clearance adjustment can affect combustion chamber sealing and directly impact engine compression pressure. This study aims to determine the effect of valve clearance variations on compression pressure in a 2005 Yamaha Mio motorcycle. The research method used was an experimental quantitative approach. Valve clearance variations tested were 0.05 mm, 0.10 mm, 0.15 mm, and 0.20 mm. Compression pressure measurements were carried out using a compression tester under cold engine conditions. The results showed that valve clearance significantly affected compression pressure. The highest compression value was obtained at a clearance of 0.05 mm with an average of 10.36 kg/cm², while the lowest value was at 0.20 mm with an average of 8.64 kg/cm². A clearance of 0.10 mm produced stable compression values in accordance with manufacturer standards. Therefore, proper valve clearance adjustment is essential to maintain engine performance and efficiency. Keywords: valve clearance, compression pressure, Yamaha Mio, four-stroke engine